O twórczym przekraczaniu granic. Przetworzenia i reprezentacje w przestrzeni sztuki - Szczęsna, Ewa (Przestrzenie Teorii, 2019)
The paper analyzes the thesis that constantly transgressing boundaries in art is a fundamental principle and essential condition for artistic progress. Crossing external (the art – other discourses) and internal (between various art genres) boundaries is analyzed on the basis of transformations (especially adaptation) and representations. Dialogue relations initialized by art crossing the boundaries are analyzed as well: reinterpretations, polemics, extensions and supplementations. There is also a discussion of the ways in which semiotic and media boundaries are trangressed, especially the semiotic and media borders that are essential for the semiotic sphere of one artistic genre for the semiotic and media sphere of the other. The article refers to examples taken from literature, film, sculpture and painting.